Pengaruh Lingkungan Kerja Terhadap Tingkat Stres dan Produktivitas Karyawan - Fatma Salsabila; Mutiara Ashifa; Nurly Fadila; Susilawati; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
The work environment on stress levels and employee productivity are interrelated and significant things. A comfortable and supportive work environment can increase productivity and reduce stress. The aim of this literature study is to obtain information and analyze articles that influence the work environment on stress levels and employee productivity. The method used to collect information is literature view methodology through sources from online media such as Mendeley, Google Scholar, Publish or Perish, and other online media. Based on the articles that have been collected, the results show that there are factors that contribute to the work environment. A comfortable work environment has a big influence on employee productivity, conversely, if the work environment is not conducive it will be the cause of decreased employee productivity